(untitled) (Research, Society and Development, 2021)
Introduction: in 2020, the world was marked by a crisis: the COVID-19 pandemic. The main measure adopted to reduce contamination is social isolation. This triggered several consequences in health, socioeconomic spheres, and interpersonal relationships, resulting in stressful conditions. Objective: to analyze in the literature what are the main consequences of social isolation on the mental health of the population during the COVID-19 pandemic. Methods: this is a narrative review of the literature, qualitative in nature. The PICO strategy (acronym for patient, intervention, comparison, outcomes) was used to elaborate the research question of this review. Results: it was found that social isolation impacts the mental health of various groups in society, generating uncertainty, fear, anxiety, economic losses and significant psychological distress, which can lead to emotional imbalance and consequent illness and death by COVID-19, as well as having repercussions on the epidemic of mental disorders in the population. Conclusion: The social isolation imposed to contain the pandemic intensifies previous challenges and vulnerabilities, making it important to implement public policies aimed at mental health.